1998
DOI: 10.1093/ije/27.4.574
|View full text |Cite
|
Sign up to set email alerts
|

A case-control study of hepatitis B and C virus infection as risk factors for hepatocellular carcinoma in Henan, China

Abstract: This is the first reported case-control study of HCC in Henan, China. This study provides further evidence that chronic HBV infection is strongly associated with the development of HCC among this population. Our results have demonstrated that HCV and HBV infection are independent and probably additive risk factors for HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 20 publications
3
61
0
Order By: Relevance
“…A total of 32 case -control studies satisfied the inclusion criteria (Xu et al, 1990;Gong et al, 1993;Zhang et al, 1993Zhang et al, , 1998Ye et al, 1994;Zhou et al, 1994;Fan et al, 1995a, b;Pan et al, 1995;Wang et al, 1996aWang et al, , b, 1999Guo and Yan, 1997;Lu, 1997;Lu and Hou, 1997;Ma et al, 1997;Shen et al, 1997;Yu et al, 1997;Zuo et al, 1997;Dai et al, 1998;Gao et al, 1998;Cui et al, 1999;Li et al, 1999Li et al, , 2002Yang et al, 1999;Zhao et al, 2000;Shi et al, 2001;Su et al, 2002;Wang, 2003;Wu et al, 2003;Zeng et al, 2003;Ding et al, 2004). Their basic characteristics are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 32 case -control studies satisfied the inclusion criteria (Xu et al, 1990;Gong et al, 1993;Zhang et al, 1993Zhang et al, , 1998Ye et al, 1994;Zhou et al, 1994;Fan et al, 1995a, b;Pan et al, 1995;Wang et al, 1996aWang et al, , b, 1999Guo and Yan, 1997;Lu, 1997;Lu and Hou, 1997;Ma et al, 1997;Shen et al, 1997;Yu et al, 1997;Zuo et al, 1997;Dai et al, 1998;Gao et al, 1998;Cui et al, 1999;Li et al, 1999Li et al, , 2002Yang et al, 1999;Zhao et al, 2000;Shi et al, 2001;Su et al, 2002;Wang, 2003;Wu et al, 2003;Zeng et al, 2003;Ding et al, 2004). Their basic characteristics are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the previous studies from China and other countries demonstrated that hepatitis B virus (HBV) or hepatitis C virus (HCV) infection, dietary exposure to aflatoxin and excessive alcohol consumption were the principal etiological factors for HCC [18][19][20][21][22][23]. The majority of people with HCC will die within 1 year of its detection.…”
Section: Introductionmentioning
confidence: 99%
“…In neighboring Bulgaria, the percentage of co-infection was 0.68% (16). It is considered that such co-infection can significantly increase the risk for development of hepatocellular carcinoma and it is common in areas with a high prevalence of hepatitis B (17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%